Effect of temperature and light on germination of 10 species of Eucalyptus from north-western NSW - Borges, Erica Rievrs; Prado-Junior, Jamir; Santana, Lucas Deziderio; Delgado, Camila Nardy; Raymundo, Diego; Campos Ribeiro, Jose Hugo; Rossatto, Davi Rodrigo [UNESP]; Carvalho, Fabricio Alvim (Csiro Publishing, 2018)
Cloud forests and savannas differ in several environmental aspects, particularly in light irradiance and water availability. Such differences can be selective for specific sets of leaves and architectural strategies to capture light and use water. In the present study we evaluated functional traits variation in a generalist species in two adjacent habitats experiencing an abrupt change in resource availability (light and water availability). We collected several leaf, stem and architectural traits of the tree species Eremanthus erythropappus (DC.) MacLeish in shrubland savanna (habitat facing higher drought stress and wind exposure) and cloud forest (shaded environment). Trees in the shrubland savanna exhibited functional trait values that enhance drought tolerance (i.e. higher wood density and leaf thickness) whereas trees in the cloud forest exhibited functional trait values that enhance light capture (i.e. taller individuals with higher leaf area and specific leaf area). Additionally, the individuals in the shrubland savanna had wider and deeper crowns, pointing that the benefits of a larger canopy area to capture light during the day and humidity from condensation at night exceed the higher risk of mechanical damage by falling debris due to high wind exposure. For all traits, variation among the individuals was lower than variation among habitats. Our results indicate the strong role of the environment as a driver of intraspecific variation and that architectural traits (usually poorly studied compared with other traits) should be included as an important parameter of variation in functional analyses when evaluating the effect of environmental conditions on tree performance.
Keywords: alternating day/night seasonal temperature; ecological restoration; germination rate; seed weight; seedlot testing; time to first germination